Characterization of Substandard Limestone Aggregates Using XRF, XRD, and SEM: Implications for Cement Paste Reinforcement in Concrete Applications - Edward Ngii; La Hamimu; Abdul Kadir; La Ode Hasan Jamilu; Adi Kumala; Slamet Slamet (MEDIA KONSTRUKSI, 2024)
This study investigates the properties of substandard limestone aggregates sourced from a quarry in Meleura Village, Muna Regency, Southeast Sulawesi, Indonesia, and explores their potential use in concrete applications. The aggregates were characterized using X-ray fluorescence (XRF), X-ray diffraction (XRD), and scanning electron microscopy (SEM) to assess their chemical composition, crystalline phases, and microstructural features. The XRF analysis revealed significant silica content, while XRD identified calcite, quartz, and dolomite as the primary phases. SEM analysis showed notable porosity and microcracks, indicating potential weaknesses. Despite these challenges, the study suggests that with appropriate treatments, such as the use of supplementary cementitious materials, these aggregates could be effectively utilized in concrete, contributing to sustainable construction practices. The findings underscore the importance of targeted reinforcement strategies to enhance aggregate performance and recommend further research on long-term durability and environmental impacts.